Síntese, caracterização e avaliação da atividade biológica de metalofármacos de sulindaco com íons lantanídeos (III) no estado sólido - Guerra, Renan Barrach [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Synthesis and characterization of complexes of the anti-inflammatory drug nonsteroidal sulindac (sulin) with the lanthanide ions (Ln3+) La3+, Ce3+, Pr3+, Nd3+, Gd3+, Tb3+ and Ho3+ in the solid state area described in this work. The characterization of the pharmaceutical and the complexes was performed using simultaneous thermogravimetry-differential scanning calorimetry (TG-DSC), differential scanning calorimetry-photovisual (DSC-photovisual), coupled thermogravimetry-infrared spectroscopy (TG-FTIR) analyses, complexometric titranion with EDTA and elemental analysis, and also use of X-ray diffraction by the powder method and vibrational spectroscopy reflectance in the infrared Fourier transform spectroscopy (FTIR). The thermal analysis results provided information concerning the thermal stability, dehydration and the thermal behavior of the compounds and along with the compleximetric titration and elemental analysis, it was possible to determine the stoichiometry of the complex as [Ln(sulin)3]XH2O. The spectroscopic results suggest that the ligand sulindac coordinates through the carboxylate group to the metals as a bidentatebrinding ligand. Tests for cytotoxicity and anti-inflammatory activity of the synthesized compounds demonstrated tha the complexes in general have very similar behavior in comparison to the drug. However, the results suggest that [Gd(sluin)3] has potential for pharmacological improvement

A síntese e caracterização de complexos do fármaco anti-inflamatório não esteroide sulindaco (sulin) com os íons lantanídeos (Ln3+) La3+, Ce3+, Pr3+, Nd3+, Gd3+, Tb3+ e Ho3+ no estado sólido são descritas neste trabalho. A caracterização dos complexos foi realizada empregando a termogravimetria-calorimetria exploratória diferencial simultânea acoplada ao espectrômetro de FTIR (TG-DSC-FTIR), DSC-fotovisual, titulação complexométrica com EDTA e análise elementar, além de utilização de difração de raios X pelo método do pó e espectroscopia vibracional de refletância na região do infravermelho com transformada de Fourier (FTIR). Os métodos termoanalíticos foram utilizados para verificar a decomposição térmica, estabilidade térmica, entalpia de desidratação, entre outras propriedades e juntamente com a titulação complexométrica e a análise elementar, foi possível determinar a estequiometria dos complexos como [Ln(sulin)3]XH2O. Através do espectro de infravermelho pode-se sugerir que o sulindaco está coordenado aos íons lantanídeos de modo bidentado e em ponte pelo grupo carboxilato. Os testes de citotoxicidade e de atividades anti-inflamatória dos compostos sintetizados demonstraram que os complexos, em geral, possuem comportamento muito semelhante ao do fármaco. Contudo, os resultados, sugerem que complexo [Gd(sulin)3] apresenta potencial para um melhoramento farmacológico
Keywords: Metais de terras raras; Metalogenia; Rare earth metals